Effects of Gehl's urban design guidelines on walkability: A virtual reality experiment in Singaporean public housing estates. (November 2022) - Silvennoinen, Heidi; Kuliga, Saskia; Herthogs, Pieter; Recchia, Daniela Rodrigues; Tunçer, Bige
Walkability has become an important theme of urban design research and practice. Evidence suggests that environmental attractiveness can have a significant impact on the amount of walking activities that take place, but relatively little research exists on which environmental features linked to attractiveness increase walkability. Using a virtual reality experiment, the present study examined the effects on walkability of three key features, as defined by Jan Gehl, an influential urban planning practitioner and theorist: liveliness, high-quality façades and low buildings. A virtual reality simulation allowed isolating the effects of these features, while avoiding confounding factors, such as the presence of shops, which has been difficult to do in past field studies. Our study confirmed that the combination of features recommended by Gehl promoted walking activity in the study's context. Further exploratory analyses suggested that improved façade quality was positively linked to walking activity, and that building height and liveliness had negligible effects. Our findings contribute to the existing understanding of walkability, which may benefit urban planning practice and models of walkability. Further research is necessary to confirm our results regarding the effects of specific features on walking activity in different contexts.